2019
DOI: 10.1111/jth.14364
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin use reduces thrombin generation potential in patients with venous thromboembolism: a randomized controlled trial

Abstract: Essentials The role of statins in hemostasis and venous thromboembolism (VTE) prophylaxis is not clear.This trial assessed whether rosuvastatin use affects thrombin generation in patients with VTE.Endogenous thrombin potential and peak were decreased by 10% and 5% with rosuvastatin therapy.These results provide basis for trials on the efficacy of statins in reducing recurrent VTE risk. SummaryBackgroundStatin therapy could form an alternative prophylactic treatment for venous thromboembolism (VTE) if statins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
1
22
1
Order By: Relevance
“…First, the observed lower mortality rate is not due to the effect of statins on LDL-C or total cholesterol levels, but rather to other "pleiotropic" mechanisms, such as platelet inhibition, reduction of inflammation, reduction of C-reactive protein, increased production of nitric oxide, or downregulation of the coagulation cascade. 6,21 This is supported by meta-analysis and metaregression of randomized controlled trials 8 and randomized clinical trial (START) 9 and several clinical studies demonstrating that statin therapy either with rosuvastatin, 21 simvastatin, 22 atorvastatin, 23,24 or cerivastatin 25 affects coagulation factors and thrombin generation. In our study, no differences in levels of total or LDL cholesterol at baseline were observed and this can be in line with this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…First, the observed lower mortality rate is not due to the effect of statins on LDL-C or total cholesterol levels, but rather to other "pleiotropic" mechanisms, such as platelet inhibition, reduction of inflammation, reduction of C-reactive protein, increased production of nitric oxide, or downregulation of the coagulation cascade. 6,21 This is supported by meta-analysis and metaregression of randomized controlled trials 8 and randomized clinical trial (START) 9 and several clinical studies demonstrating that statin therapy either with rosuvastatin, 21 simvastatin, 22 atorvastatin, 23,24 or cerivastatin 25 affects coagulation factors and thrombin generation. In our study, no differences in levels of total or LDL cholesterol at baseline were observed and this can be in line with this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…Mechanisms by which androgens might cause IHD have not been extensively investigated, but likely involve coagulation and red blood cell attributes. Several haemostatic and thrombotic factors, such as thromboxane A 2 [44,45], endothelin-1 [46][47][48], nitric oxide [44,49] and possibly thrombin [50,51], may be driven by androgens and likely play a role in IHD [52][53][54]. Von Willebrand factor [55] and asymmetric dimethylarginine [56] are also modulated by statins and may cause IHD [4,57], whether they are driven by testosterone is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which androgens might cause IHD have not been extensively investigated, but likely involve coagulation and red blood cell attributes. Several haemostatic and thrombotic factors, such as thromboxane A 2 ( Pignatelli et al, 2012 ; Ajayi and Halushka, 2005 ), endothelin-1 ( Polderman et al, 1993 ; van Kesteren et al, 1998 ; Sahebkar et al, 2015 ), nitric oxide ( Pignatelli et al, 2012 ; Rosselli et al, 1998 ) and possibly thrombin ( Orsi et al, 2019 ; Ferenchick et al, 1995 ), may be driven by androgens and likely play a role in IHD ( Schooling et al, 2018b ; Zhao, 2018 ; Nikpay et al, 2015 ). Von Willebrand factor ( Sahebkar et al, 2016 ) and asymmetric dimethylarginine ( Serban et al, 2015 ) are also modulated by statins and may cause IHD ( Aday and Ridker, 2018 ; Au Yeung et al, 2016 ), whether they are driven by testosterone is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The START (The STAtins Reduce Thrombophilia) trial published in 2019 randomized 245 patients with a history of VTE (48.6% unprovoked) who have completed a course of anticoagulation to rosuvastatin 20 mg daily or no statin for 4 weeks (29). All patients stopped vitamin K antagonists for one month prior to enrollment.…”
Section: Discussionmentioning
confidence: 99%